Centennial records of Polycyclic aromatic hydrocarbons and black carbon in Altay Mountains peatlands, Xinjiang, China - Luo, Nana; Wen, Bolong; Bao, Kunshan; Yu, Rui; Sun, Jing; Li, Xiujun; Liu, Xingtu (Frontiers in Ecology and Evolution, 2022)
Black carbon (BC) and polycyclic aromatic hydrocarbons (PAHs) are often used to indicate anthropogenic impacts on natural environmental changes during the past century. In this study, a 60 cm peat core was collected from the Jiadengyu (JDY) peatland in Altay Mountain and dated by the 137Cs and 210Pb methods. The total organic carbon, BC and PAHs contents in JDY peat core were 17.09-47.2%, 1.14-72.6 mg g-1 and 260.58-1610.77 ng·g-1, respectively. The δ13CBC ranged from -31.5‰ to -29.43‰, with an average of -30.56‰. Scanning electron microscope (SEM) showed that the BC particles in the peat were lumpy or irregular in shape and retained the structure of plant fiber. The PAHs ratios, δ13CBC and the SEM result indicated the dominant biomass combustion source of BC in the peatland. The BC content increased from 1950 to 1980 and decreased after 1980. The change of BC and δ13CBC is different from the national BC emission pattern, probably reflecting the impact of local agricultural exploration and thus crop burning increase.